Comparison between the magnetic method data of pseudogravity transformation with gravity anomaly data from satellite imagery in the surrounding of the Sutami Dam to identify subsurface formations. Issue 1 (1st January 2022) - Sutasoma, M; Susilo, A; Sunaryo,; Suryo, E A; Minardi, S; Cahyo, R H D
Abstract: Research has been carried out to determine the subsurface formations in the Sutami dam area and its surroundings using the magnetic method of pseudogravity transformation and satellite imagery gravity anomaly data. This study aims to compare the subsurface formations in the area around the Sutami Dam between the data of the pseodu-gravity transformation magnetic method and the gravity anomaly data of satellite imagery. Data acquisition using the pseudogravity magnetic transformation method was carried out using the Proton Precession Magnetometer (PPM) Scientrex Model G-8 with a spacing of 300 meters. Satellite imagery gravity anomaly data was taken from the Gravity Model Plus (GGM plus) with a spacing of 220 meters. The radius of geomagnetic data acquisition was 15 km. The number of data for the magnetic method of pseudogravity transformation was 1, 372 measurement points and satellite imagery gravity anomaly data was 3, 000 measurement points. The results showed that the rock formations from the magnetic method of pseudogravity transformation and satellite gravity anomaly data were compatible. There are 4 types of subsurface formations in the study area, namely soil (Δρ = 1.6 g/cm 3 ), Butak Volcanic Product (Δρ = 2 g/cm 3 ), Tuff Deposit (Δρ = 2.1 g/cm 3 ) and Campurdarat Formation (Δρ = 2.6 g/cm 3 ).